Comparison between CAD models using modification ratio calculation. Issue 10 (3rd October 2019) - Eltaief, Ameni; Remy, Sébastien; Louhichi, Borhen; Ducellier, Guillaume; Eynard, Benoit
ABSTRACT: Engineering changes management has become a crucial task in product lifecycle management. Indeed, the good management of the modifications enables saving both money and time concerning the important competition existing in the market where the majority of mechanical products are complex systems and generally composed of sub-systems. Computer-aided design (CAD) is the use of computer systems to aid in the creation, the modification, the analysis, and/or the optimisation of a design. Actually, CAD softwares are used to increase the productivity of the designer and improve the quality of design. Therefore, researchers aim to improve those CAD systems in order to increase their efficiency and facilitate the designer task. Consequently, the objective of the authors is to develop a model to help the user to manage modifications affecting a simple part of an assembly CAD model, before propagating it to the whole assembly model. Thus, as a first step, the initial and the modified version of a considered part have to be compared in order to detect the affected features, pick up the topologic and geometric modifications, and then calculate the ratio of modification. This ratio measures the importance of changes that affect the initial part, and it will be useful later on while propagating this change.